Foreign Direct Investment and Agglomeration in Six southern California Counties - Martinez, Jose N.; Prager, Fynnwin; Kattan, Carlos (Journal of Applied Business and Economics, 2017)
This paper analyzes data on Foreign Owned Enterprises (FOEs) in Southern California. Spatial agglomeration is higher with respect to industrial sector than to country of origin. Cities with high FOE concentrations have larger labor forces, lower unemployment rates, higher sales, more workers, and higher 3-year growth rate in sales volume than cities with lower FOE concentration. These findings suggest that Southern California cities receiving a large number of FOEs benefit from this agglomeration. Similarly, potential FOEs might benefit by locating in areas with high concentrations of FOEs, like Los Angeles County and the Southern California region in general.